Misoprostol rectally in uterine atony unresponsive to conventional treatment. - Sandoval, José (2015)
OBJECTIVES: To evaluate the efficacy, tolerability and safety of misoprostol rectally to control uterine atony. DESIGN: clinical trial. PLACE: National Hospital "Sergio E. Bernales" Collique, Lima, during the period September 1998 to December 1999. MATERIAL AND METHODS: Patients who had postpartum hemorrhage (PPH) by uterine inertia, which persists despite the application of uterine massage , oxytocics and ergot. Seven patients were administered 800 mcg of misoprostol in the rectal vault, and every 5 minutes an additional 200 mg was added if bleeding persisted. RESULTS: In 7 patients the bleeding was controlled by an average of 5.8 minutes. In no case they were presented side effects. It was applied in only 3 patients 800 ug and 1000 ug 4 women total dose of misoprostol. By severe hemorrhage in 7 cases hemoglobin dropped an average of 3.4 mg%. CONCLUSIONS: Misoprostol rectally is effective, safe and well tolerated to control PPH from uterine atony. It comes as a great alternative to control PPH problems in remote areas do not have adequate technical resources.